Protocol for a core outcome set for pharmacological treatments in hospitalised patients with acute viral respiratory infections (COSAVRI) - Declan Devane; Matthias Briel; Sanjay Bhagani; Nadine Boesten; Stephanie Buchholz; Estefania Callejas De Luca; Jeremie Guedj; Anastasia Koryakina; Kavita Kothari; Karine Lacombe; Patrick W. Mallon; Clément R. Massonnaud; et al. (PLoS ONE, 2025)
Background Acute viral respiratory infections (AVRIs) rank among the most common causes of hospitalisation worldwide, imposing significant healthcare burdens and driving the development of pharmacological treatments. However, inconsistent outcome reporting across clinical trials limits evidence synthesis and its translation into clinical practice. A core outcome set (COS) for pharmacological treatments in hospitalised adults with AVRIs is essential to standardise trial outcomes and improve research comparability. Objective To develop an internationally agreed COS for pharmacological treatments in hospitalised adults ≥18 years with acute viral respiratory infections (COSAVRI) through stakeholder agreement. Methods This protocol follows a four-stage development process in accordance with Core Outcome Set Handbook guidelines. Stage 1 comprises a rapid scoping review of randomised controlled trials (2015–2025) to systematically catalogue patient-relevant outcomes reported in pharmacological AVRI treatment studies. Semi-automated screening and data extraction will employ machine learning and large language models, with human verification. Stage 2 involves an online Real-Time Delphi survey with international stakeholders, including healthcare professionals, researchers, patients/caregivers, and policymakers, to prioritise identified outcomes using a 9-point scale. Stage 3 consists of structured online consensus meetings utilising anonymous electronic voting to finalise the COS. Stage 4 focuses on dissemination and implementation through academic publications, conferences, and stakeholder engagement. Expected outcomes COSAVRI will provide a standardised minimum set of outcomes for measuring and reporting in future pharmacological trials involving hospitalised adults with AVRIs. This initiative will enhance evidence synthesis, reduce research waste, support regulatory decision-making, and improve pandemic preparedness by facilitating the rapid deployment of harmonised outcomes in trial protocols.